Lithium ion battery positive electrode material, preparation method thereof and lithium ion battery
Through the thermal polymerization treatment of large π system polyimide COF composite material and the combination of carbon black and polyvinyl difluoride, the renewability, cost and environmental friendliness of the cathode material of lithium-ion battery are solved, and high capacity and Stable lithium-ion battery positive electrode material, suitable for lithium-ion battery applications.
Patent Information
- Application Number
- CN202411213884.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2025-01-10
AI Technical Summary
The existing lithium-ion battery positive electrode materials have problems such as non-renewable, expensive, serious environmental pollution, and limited theoretical capacity. The poor solubility of organic materials in liquid electrolytes leads to poor electrochemical performance.
The polyimide COF composite material with a large π system is used as the electrode active material, and the thermal polymerization of melamine and 3,4,9,10-perylene tetracarboxylic acid dianhydride is combined with carbon black and polyvinyl difluoride, and coated with carbon black and polyvinyl difluoride. The lithium-ion battery positive electrode material is prepared on pure aluminum foil to form an electrode with high reversible capacity and cycle stability.
The cathode material of lithium-ion battery with high reversible capacity and excellent rate performance is realized, which reduces production costs and improves the stability of the material in electrolyte, and is suitable for the wide application of lithium-ion batteries.
Smart Images

Figure CN119285938A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a lithium ion battery positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As an important energy storage technology, lithium-ion batteries are widely used in many fields such as electric vehicles, large energy storage power stations, consumer electronics, etc., and play an increasingly important role in today's society. Lithium-ion batteries are composed of several components such as positive electrode materials, negative electrode materials, conductive agents, binders, electrolytes, and separators. Among them, the electrode active materials (positive electrode and negative electrode) are the core of the battery.
[0003] Inorganic transition metal oxide materials are currently the mainstream commercial lithium-ion battery positive electrode materials. However, they have major problems such as being non-renewable, expensive, causing serious environmental pollution, and having limited theoretical capacity. It is becoming increasingly difficult to meet society's demand for green and friendly high-performance electrode materials.
[0004] Organic electrode materials have attracted widespread attention due to their abundant resources, environmental friendliness, and high structural designability. Carbonyl compounds have the advantages of high theoretical capacity and outstanding chemical stability. Therefore, organic materials, especially polyimides rich in carbonyl functional groups, have become one of the materials most likely to replace inorganic positive electrodes in the future because of their simple structure (containing only C, H, O), light weight, abundant resources, and environmental friendliness.
[0005] However, although some organic materials are more stable in the solvated state than in the solid aggregate state, they face serious dissolution problems in the liquid electrolyte of rechargeable metal ion batteries, resulting in poor electrochemical performance. At the same time, batteries tested during the charge and discharge process often suffer from significant performance degradation. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a positive electrode material for a lithium ion battery.
[0009] To solve the above technical problems, the present invention provides the following technical solution: a polyimide COF composite material with a large π system is used as an electrode active material, wherein the polyimide COF composite material is obtained by thermal polymerization of melamine and 3,4,9,10-perylenetetracarboxylic dianhydride.
[0010] Another object of the present invention is to provide a method for preparing a positive electrode material for a lithium ion battery.
[0011] In order to solve the above technical problems, the present invention provides the following technical solution: comprising: coating a polyimide COF composite material, carbon black and polyvinylidene fluoride on pure aluminum foil to obtain a positive electrode for a lithium-ion battery.
[0012] As a preferred embodiment of the method for preparing the positive electrode material for lithium-ion batteries of the present invention, the molar ratio of melamine to 3,4,9,10-perylenetetracarboxylic dianhydride is 1:1-2.
[0013] As a preferred solution of the method for preparing the positive electrode material of a lithium-ion battery of the present invention, the thermal polymerization treatment comprises high-temperature calcination.
[0014] As a preferred embodiment of the method for preparing the positive electrode material for lithium-ion batteries of the present invention, the temperature of the thermal polymerization treatment is 300-350°C.
[0015] As a preferred solution of the method for preparing the positive electrode material for lithium-ion batteries of the present invention, the time of the thermal polymerization treatment is 3 to 5 hours.
[0016] Another object of the present invention is to provide a lithium ion battery.
[0017] In order to solve the above technical problems, the present invention provides the following technical solution: the lithium-ion battery positive electrode material is used as the positive electrode, and the pure lithium sheet is used as the counter electrode to assemble into a lithium-ion button-type half-cell.
[0018] As a preferred embodiment of the lithium-ion battery of the present invention, the lithium-ion button-type half-cell has a charge and discharge voltage range of 1.5 to 4.5 V and a current density of 0.1 A g -1 Under the condition of , the capacity after 70 cycles>110mAhg -1 .
[0019] As a preferred embodiment of the lithium-ion battery of the present invention, the lithium-ion button-type half-cell has a charge and discharge voltage range of 1.5 to 4.5 V and a current density of 0.2 A g -1 Under the condition of -1 .
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention prepares a polyimide COF organic positive electrode material with a large system by a thermal polymerization method. During the thermal polymerization process, the polymerization of melamine and 3,4,9,10-perylenetetracarboxylic dianhydride is completed in one step, which can realize the construction of a large system.
[0022] (2) The present invention uses 3,4,9,10-perylenetetracarboxylic dianhydride and melamine as organic monomers to prepare polymer materials, and can achieve the regulation of large system pores by expanding building units. The raw materials are designable, the structure is simple, and the cost is low.
[0023] (3) The polyimide COF organic cathode material with a large system prepared by the method of the present invention has high reversible capacity, very good cycle stability and rate performance, and has broad application prospects in the field of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 This is a morphology picture of the polyimide COF composite material prepared in Example 1.
[0026] Figure 2 This is the X-ray diffraction pattern of the positive electrode material prepared in Example 1.
[0027] Figure 3 This is a rate performance diagram of a lithium-ion button-type half-cell assembled from the positive electrode material of Example 1.
[0028] Figure 4 The graph shows the cycle performance of lithium-ion button-type half-cells assembled from the positive electrode materials of Example 1 and Comparative Example 1.
[0029] Figure 5 The cycling performance and rate performance of lithium-ion button-type half-cells assembled from the electrode materials prepared in Comparative Examples 2 and 3 and the electrode material prepared in Example 1 are compared.
[0030] Figure 6 The cycling performance and rate performance of lithium-ion button-type half-cells assembled from the electrode materials prepared in Comparative Examples 4 and 5 and the electrode material prepared in Example 1 are compared.
[0031] Figure 7The cycling performance and rate performance of lithium-ion button-type half-cells assembled from the electrode material prepared in Comparative Example 6 and the electrode material prepared in Example 1 are compared. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0035] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0036] The application test method in the present invention refers to:
[0037] The positive electrode material prepared in the embodiment or comparative example was used as the positive electrode, and the pure lithium sheet was used as the counter electrode to assemble a lithium ion button half-cell for electrochemical testing. The charge and discharge voltage range of the test was 1.5 to 4.5 V, and the tests were all carried out at room temperature.
[0038] Example 1
[0039] This embodiment provides a method for preparing a positive electrode of a lithium ion battery, specifically:
[0040] 1) melamine and 3,4,9,10-perylenetetracarboxylic dianhydride are uniformly mixed in a molar ratio of 1:1, and ground to obtain a prepolymer;
[0041] 2) The prepolymer is calcined in a tubular furnace in an air atmosphere for thermal polymerization at a calcination temperature of 325° C. for a holding time of 4 h to obtain a polyimide COF composite material with a large π system, denoted as PI-COF. Figure 1 This is the morphology of the material.
[0042] 3) The PI-COF obtained in step 2) is mixed with carbon black and polyvinyl difluoride in a mass ratio of 6:3:1 and then evenly coated on pure aluminum foil (99.6%) by a coating method to prepare a positive electrode material. Figure 2The X-ray diffraction pattern of the positive electrode material shows a series of sharp peaks, indicating that the material has good crystallinity.
[0043] Figure 3 The figure is the rate performance diagram of the positive electrode material of this embodiment as a positive electrode material for lithium-ion batteries. It can be seen that the electrochemical performance can remain stable at different current densities and when the current rate is restored to 0.05A g -1 The capacity of PI-COF can be restored to 100 mAh g -1 .
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) is not polymerized with melamine, but is directly mixed with carbon black and polyvinylidene fluoride in a mass ratio of 6:3:1 and then uniformly coated on pure aluminum foil (99.6%) by a coating method to prepare the positive electrode material of this comparative example.
[0046] Figure 4 The cycle performance diagram of the positive electrode material of Example 1 and the positive electrode material of Comparative Example 1 as positive electrode materials for lithium-ion batteries shows that PI-COF exhibits a satisfactory discharge specific capacity of 103 mAh g in the initial cycle. -1 , with a Coulombic efficiency of 92.77% (CE%). From the second cycle onwards, it showed significant capacity retention after long-term cycling. After 100 cycles, the capacity was still 107 mAh g -1 Although pure PTCDA has a high initial discharge specific capacity, its capacity decreases rapidly in subsequent cycles.
[0047] Comparative Example 2
[0048] The difference between this comparative example and Example 1 is that the calcination temperature after the polymerization of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and melamine is adjusted to 265°C, and the remaining steps and processes are referred to Example 1 to obtain the positive electrode material of this comparative example, which is recorded as PI-COF-265°C.
[0049] Comparative Example 3
[0050] The difference between this comparative example and Example 1 is that the calcination temperature after the polymerization of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and melamine is adjusted to 385°C, and the remaining steps and processes are referred to Example 1 to obtain the positive electrode material of the comparative example, which is recorded as PI-COF-385°C.
[0051] The relevant properties of the positive electrode materials prepared in Comparative Examples 2 and 3 as positive electrode materials for lithium ion batteries were measured and compared with those in Example 1. The results are shown in Table 1 and Figure 5 shown.
[0052] Table 1
[0053] Capacity / cycle number / current density Rate capacity / current density Example 1 <![CDATA[113.9mAhg -1 / 70 / 0.1Ag -1 ]]> <![CDATA[75.6mAhg -1 / 2Ag -1 ]]> Comparative Example 2 <![CDATA[38.2mAhg -1 / 70 / 0.1Ag -1 ]]> <![CDATA[48.2mAhg -1 / 2Ag -1 ]]> Comparative Example 3 <![CDATA[109mAhg -1 / 65 / 0.1Ag -1 ]]> <![CDATA[1.5mAhg -1 / 2Ag -1 ]]>
[0054] Figure 5 (a) and (b) are comparisons of the cycle performance of lithium-ion button-type half-cells assembled from the electrode materials prepared in Comparative Examples 2 and 3 and the electrode materials prepared in Example 1, respectively. Figure 5 (c) and (d) are comparisons of the rate performance of lithium-ion button-type half-cells assembled from the electrode materials prepared in Comparative Examples 2 and 3 and the electrode material prepared in Example 1.
[0055] From Table 1 and Figure 5 It can be seen that the calcination temperature has a certain influence on the capacity and stability of the obtained electrode material. The initial capacity and stability of Example 2 are lower than those of Example 1, and the capacity of Example 3 is better than that of Example 2. However, overall, the capacity and stability of the PI-COF of Example 1 are the best.
[0056] Example 2
[0057] The difference between this embodiment and embodiment 1 is that the molar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) to melamine is adjusted to 2:1, and the remaining steps and processes are referred to embodiment 1 to obtain the positive electrode material of this embodiment, which is recorded as PI-COF-2:1.
[0058] It has been determined that the positive electrode material prepared in this embodiment can achieve the same technical effect as that of embodiment 1.
[0059] Comparative Example 4
[0060] The difference between this comparative example (PI-COF-1:2) and Example 1 is that the composite millimolar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and melamine is 1:2, which is then mixed with carbon black and polyvinyl difluoride in a mass ratio of 6:3:1 and evenly coated on pure aluminum foil (99.6%) by a coating method to prepare the positive electrode material of this comparative example.
[0061] Comparative Example 5
[0062] The difference between this comparative example (PI-COF-1:3) and Example 1 is that the molar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) to melamine is 1:3, which is then mixed with carbon black and polyvinyl difluoride in a mass ratio of 6:3:1 and evenly coated on pure aluminum foil (99.6%) by a coating method to prepare the positive electrode material of this comparative example.
[0063] Comparative Example 6
[0064] The difference between this comparative example (PI-COF-1:3) and Example 1 is that the molar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) to melamine is 3:1, which is then mixed with carbon black and polyvinyl difluoride in a mass ratio of 6:3:1 and then evenly coated on pure aluminum foil (99.6%) by a coating method to prepare the positive electrode material of this comparative example.
[0065] The relevant properties of the positive electrode materials prepared in Comparative Examples 4 to 6 as positive electrode materials for lithium ion batteries were measured and compared with those in Example 1. The results are shown in Table 2 and Figure 6 , Figure 7 shown.
[0066] Table 2
[0067] Capacity / cycle number / current density Rate capacity / current density Example 1 <![CDATA[106.7mAhg -1 / 50 / 0.1Ag -1 ]]> <![CDATA[75.6mAhg -1 / 2Ag -1 ]]> Comparative Example 4 <![CDATA[94.7mAhg -1 / 50 / 0.1Ag -1 ]]> <![CDATA[53.2mAhg -1 / 2Ag -1 ]]> Comparative Example 5 <![CDATA[91.6mAhg -1 / 50 / 0.1Ag -1 ]]> <![CDATA[27.4mAhg -1 / 2Ag -1 <!-- 4 -->]]> Comparative Example 6 <![CDATA[26.12mAhg -1 / 50 / 0.1Ag -1 ]]> <![CDATA[27.2mAhg -1 / 2Ag -1 ]]>
[0068] Figure 6 (a) and (b) are comparisons of the cycle performance of lithium-ion button-type half-cells assembled from the electrode materials prepared in Comparative Examples 4 and 5 and the electrode materials prepared in Example 1, respectively. Figure 5 (c) and (d) are rate performance comparisons of lithium-ion button-type half-cells assembled from the electrode materials prepared in Comparative Examples 4 and 5 and the electrode materials prepared in Example 1, respectively.
[0069] From Table 2 and Figure 6 It can be seen that the composite ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and melamine has a significant effect on the performance of the obtained material. Although the initial capacity of comparative example 4 is higher and the rate performance is better, its capacity decreases rapidly after cycling, and Figure 6 (a) It can be seen that the charging and discharging capacities of Comparative Example 4 are relatively dispersed, the efficiency is low, and the stability is poor.
[0070] Figure 7 (a) is a comparison of the cycle performance of lithium-ion button half-cells assembled from the electrode material prepared in Comparative Example 6 and the electrode material prepared in Example 1, and (b) is a comparison of the rate performance of lithium-ion button half-cells assembled from the electrode material prepared in Comparative Example 6 and the electrode material prepared in Example 1.
[0071] From Table 2 and Figure 7 It can be seen that the composite ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and melamine has a significant effect on the performance of the obtained material. The capacity of Comparative Example 6 after the cycle is much lower than that of Example 1 from the initial capacity, and Figure 7 (a) It can be seen that the charge and discharge capacity of Comparative Example 6 is lower than that of Example 1.
[0072] The present invention prepares a polyimide COF based on the rigid macro-system of PTCDA by polymerizing 3,4,9,10-perylenetetracarboxylic dianhydride and melamine, and the COF with strong covalent bond connection ensures its chemical stability and thermal stability in the redox process; the diversity of COF redox active groups and the adjustable planar conjugated structure give the carriers great flexibility, so that they can be freely transmitted on the planar skeleton, thus helping to improve the conductivity of the material. At the same time, the large molecular weight of the polymer further enhances its insolubility in liquid electrolytes, which helps to improve the stability of the electrode material in the electrolyte.
[0073] 3,4,9,10-Perylenetetracarboxylic dianhydride monomer itself has a rigid structure, but is easily soluble in organic electrolytes. During the redox reaction, the solvent molecules in the liquid electrolyte are easily co-inserted into the organic solid together with the embedded metal ions, resulting in the destruction of the organic aggregated solid and the accelerated dissolution of the organic electrode molecules. The CN in the PTCDA structure provides active sites and high redox potential. The C=N formed between 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and melamine provides another active site. The synergistic effect of CN and C=N provides high energy density for lithium-ion battery positive electrode materials. At the same time, due to the planar conjugated structure and hierarchical pores, the honeycomb porous structure formed by micropores and mesopores has sufficient active sites exposed. The ordered pore structure and large specific surface area of COF are conducive to the diffusion and penetration of ions in the electrolyte, achieving high discharge capacity and rate performance.
[0074] Organic porous materials have excellent physical and chemical stability. Among them, COF materials have the advantages of pre-designed planar conjugated structure, adjustable pore size, and diversified building units, which make COF highly effective in material transport pathways and specific electroactive groups.
[0075] Therefore, after grinding, 3,4,9,10-perylenetetracarboxylic dianhydride and melamine react in equal molar amounts to form a monomer salt, and then the obtained monomer salt is thermally imidized in the solid state to form a covalent bond to construct a highly stable conjugated skeleton and realize a large system of covalent cross-linking. The free transmission of carriers on this unique skeleton structure further improves the conductivity of the material. At the same time, this planar conjugated structure further reduces the dissolution of the material in the electrolyte, making the material more stable. Electrochemical experimental data show that the electrode material has good conductivity and is a lithium-ion battery positive electrode with a stable cycle life.
[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A positive electrode material for a lithium-ion battery, characterized in that: A polyimide COF composite material with a large π system is used as an electrode active material, wherein the polyimide COF composite material is obtained by thermal polymerization of melamine and 3,4,9,10-perylenetetracarboxylic dianhydride.
2. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, wherein: The method comprises: a polyimide COF composite material, carbon black and polyvinylidene fluoride are mixed and coated on pure aluminum foil to obtain a positive electrode of a lithium-ion battery.
3. The method for preparing a positive electrode material for a lithium ion battery according to claim 2, characterized in that: The preparation of the polyimide COF composite material includes: Melamine and 3,4,9,10-perylenetetracarboxylic dianhydride are mixed and ground to obtain a prepolymer; The prepolymer is subjected to thermal polymerization treatment to obtain a polyimide COF composite material.
4. The method for preparing a positive electrode material for a lithium ion battery according to claim 2, wherein: The molar ratio of melamine to 3,4,9,10-perylenetetracarboxylic dianhydride is 1:1-2.
5. The method for preparing a positive electrode material for a lithium ion battery according to claim 2, characterized in that: The thermal polymerization treatment comprises high temperature calcination.
6. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: The temperature of the thermal polymerization treatment is 300-350°C.
7. The method for preparing a positive electrode material for a lithium ion battery according to claim 6, characterized in that: The thermal polymerization treatment time is 3 to 5 hours.
8. A lithium ion battery using the lithium ion battery positive electrode material according to claim 1.
9. The lithium-ion battery according to claim 8, characterized in that: The lithium-ion battery positive electrode material is used as the positive electrode and the pure lithium sheet is used as the counter electrode to assemble a lithium-ion button-type half-cell; The lithium ion button half-cell has a charge and discharge voltage range of 1.5 to 4.5 V and a current density of 0.1 Ag. -1 Under the condition of , the capacity after 70 cycles is >110mAh g -1 .
10. The lithium ion battery according to claim 9, characterized in that: The lithium ion button half-cell has a charge and discharge voltage range of 1.5 to 4.5 V and a current density of 0.2 Ag. -1 Under the condition of -1 .